Centella asiatica extract cream inhibited microphthalmia-associated transcription factor (MITF) expression and prevented melanin amount increase in Guinea pig skin exposed to ultraviolet-B - Fatri Idana; Anak Agung Gde Putra Wiraguna; Ni Wayan Winarti (Neurologico Spinale Medico Chirurgico, 2022)
Background: Centella asiatica has been popularly used in cosmetic products, especially due to its antioxidant benefits in soothing and healing wounds. However, the inhibition of melanogenesis in the content of Centella asiatica has not been widely studied. This study aimed to prove the effectiveness of 10% Centella asiatica cream on male Guinea pig (Cavia porcellus) skin exposed to UVB. Methods: The randomized posttest-only control group study was conducted on 36 Guinea pigs aged 3-months, body weight 300-350 grams with a healthy skin condition. They were randomly divided into two groups; each consists of 18 Guinea pigs. The first group was a control group given base cream 20-minutes before and 4-hours after UVB exposure, 3-times-a-week for two weeks. The second group was the treatment group given 10% Centella asiatica cream and expose to UVB with the same procedure. The histopathological preparations were made using a punch biopsy after intervention was completed. Immunohistochemical staining was performed to measure the expression of microphthalmia-associated-transcription-factor (MITF) and Masson-Fontana to measure the amount of melanin. Data analysis was conducted to compare the results in both groups. Results: The treatment group had a significantly lower mean MITF expression (13.61 ± 5.36 vs. 27.24 ± 6.50%) and melanin amount (5.95 ± 3.81 vs. 16.59 ± 5.77%) (p < 0.001) compared to the control group. Conclusion: The administration of cream consists of Centella asiatica extract 10% effectively inhibits the expression of MITF and prevented the increase of melanin amount in male guinea pigs (Cavia porcellus) exposed to UVB.